2021
DOI: 10.1186/s40798-021-00392-w
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated with Hip and Groin Pain in Elite Youth Football Players: A Cohort Study

Abstract: Background Despite hip and groin pain being commonly reported in elite youth football players, little evidence on risk factors exists. Risk factors in adult football players include reduced hip adductor strength and hip adductor/abductor strength ratios, and lower Copenhagen Hip and Groin Outcome Score (HAGOS) subscale scores. It is unknown if these factors are also predictive of pain development in youth football players. Objective To identify whe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 33 publications
(62 reference statements)
1
0
0
Order By: Relevance
“…Hölmich et al [19] reported that recovery from groin injury takes at least 1 week in 40% of cases, and more than a month in 10% of players. Thorborg et al [46] found that 49% of sub-elite players reported groin pain during the last season and 31% of them reported pain for more than 6 weeks; furthermore, lower HAGOS subscale scores were found in the beginning of the new season in players who reported groin pain in the previous season compared with players who did not report it [38]. These indings are in line with those reported in the current study.…”
Section: Soccersupporting
confidence: 91%
“…Hölmich et al [19] reported that recovery from groin injury takes at least 1 week in 40% of cases, and more than a month in 10% of players. Thorborg et al [46] found that 49% of sub-elite players reported groin pain during the last season and 31% of them reported pain for more than 6 weeks; furthermore, lower HAGOS subscale scores were found in the beginning of the new season in players who reported groin pain in the previous season compared with players who did not report it [38]. These indings are in line with those reported in the current study.…”
Section: Soccersupporting
confidence: 91%
“…Furthermore, physical characteristics of patients with groin pain have been reported to include decreased hip adductor muscle strength 3 , 4 ) and increased hip abduction range of motion 4 ) . Furthermore, high school soccer players have also been reported to develop groin pain more frequently 5 , 6 ) .…”
Section: Introductionmentioning
confidence: 99%